When Fitness Becomes Content: The Role of Digital Creation Motivation in Youth Exercise Interest - Nur Alam Rahmatullah; Carsiwan; Lutfan Ananda Antariksa (Universitas Negeri Semarang, 2026)
The increasing trend of documenting physical activity on social media has transformed exercise into a form of digital content, yet its influence on youth exercise interest remains underexplored. This study aims to examine the effect of digital content creation motivation on exercise interest among young people. A quantitative approach was employed using a survey of 250 respondents aged 15–30 years, selected through purposive sampling. All participants were active social media users who had experience producing or engaging with exercise-related content. The research instrument consisted of 33 items adapted from motivation and exercise behavior theories, with 24 items retained after validity and reliability testing. Data were analyzed using SPSS through descriptive statistics, classical assumption tests, and simple linear regression. The results indicate that digital content creation motivation has a positive and significant effect on exercise interest (β = 0.566, p < 0.001), accounting for 32% of the variance (R² = 0.320). This finding suggests that young people tend to show greater interest in exercising when their physical activities can be documented and shared as digital content. The magnitude of the explained variance indicates that digital content creation motivation is a meaningful predictor of exercise interest. These findings conclude that digital content creation functions as a psychological and social stimulus that enhances youth engagement in physical activity. The study contributes theoretically to digital behavior research and offers practical implications for developing social media–based health campaigns to promote active lifestyles among young people.